2006
DOI: 10.1542/peds.2005-1255
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Septal Defect With Secondary Left Ventricular–to–Right Atrial Shunt Is Associated With a Higher Risk for Infective Endocarditis and a Lower Late Chance of Closure

Abstract: OBJECTIVE. Although ventricular septal aneurysm may diminish or even close the shunt through the ventricular septal defect (VSD), developing a left ventricular–to–right atrial (LV-RA) shunt may be unfavorable. This study sought to clarify this issue on the basis of an extended observation of such patients. METHODS. Sixty-eight patients (1201 patient-years) who had small perimembranous VSD and LV-RA shunt and were not operated on before 6 years of age were studied. RESULTS. The ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 22 publications
1
9
1
3
Order By: Relevance
“…Wu et al reported that VSD with secondary LV-RA shunt is associated with a higher risk for infective endocarditis, but still had a low chance for late improvement and even closure. 5 In the present series, the event-free probability was not significantly different in both groups. LV-RA shunt may not aggravate the hemodynamic changes in patients with mild VSD, but may contribute to congestive heart failure and the need for surgical intervention in patients with a large VSD.…”
Section: Discussioncontrasting
confidence: 49%
“…Wu et al reported that VSD with secondary LV-RA shunt is associated with a higher risk for infective endocarditis, but still had a low chance for late improvement and even closure. 5 In the present series, the event-free probability was not significantly different in both groups. LV-RA shunt may not aggravate the hemodynamic changes in patients with mild VSD, but may contribute to congestive heart failure and the need for surgical intervention in patients with a large VSD.…”
Section: Discussioncontrasting
confidence: 49%
“…In the surgical operations, a patch repair should be performed on the right atrial side in order to prevent atrioventricular block [ 59 , 94 ]. In long-term follow-up (up to 19.7 years) 17% of the LV-RA shunts spontaneously closed, while 8.5% developed IE during follow-up [ 105 ]. The nature of spontaneous closure was proven, by surgical exploration, to be aneurysmal transformation of the tricuspid septal leaflet [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…They recommend closing essentially all Gerbode defects. In a more recent follow-up study from same group, Wu et al 8 reclassified the aneurysmal transformation in patients with LV-RA shunts, and reported that the aneurysmal transformation involving the anterior and septal leaflets of tricuspid valve (double sac) was found in 85%, whereas only the septal leaflet (single sac) was involved in 15%. Perimembranous VSD may diminish in size or spontaneously close by "aneurysmal transformation" (i.e., adherence of septal or ATL tissue of the tricuspid valve or adjacent tissue onto the VSD), but this may cause LV-RA shunts, as well as subaortic ridges.…”
Section: Discussionmentioning
confidence: 99%
“…7 Type A morphology was closely associated with the development of LV-RA shunt while types C and D were most commonly seen in those spontaneously closed defects and those with only interventricular shunt. In a more recent follow-up study from same group, Wu et al 8 reclassified the aneurysmal transformation in patients with LV-RA shunts, and reported that the aneurysmal transformation involving the anterior and septal leaflets of tricuspid valve (double sac) was found in 85%, whereas only the septal leaflet (single sac) was involved in 15%. In the case presented, a single sac of ATL forming an aneurysm, covering the VSD and causing LV-RA shunt has been described.…”
Section: Discussionmentioning
confidence: 99%